Art in Israel Today. - The Detroit Institute of Arts, Detroit (Detroit : The Detroit Insitute of Arts, 1991)
Gershuni, Moshe ; Kadishman, Menashe ; Kupferman, Moshe ; Gitlin, Michael ; Goldstein, Zvi ; Tevet, Nahum ; Berest, Dganit ; Borkovsky, Joshua ; Klasmer, Gabi
An exhibition sponsored by the American-Israel Education Institute and the Friends of Modern Art.
Art in Israel Today, The Detroit Institute of Arts, Detroit, May 24 - August 18, 1991
boek